Changes in 5S rDNA Chromatin Organization and Transcription during Heterochromatin Establishment in Arabidopsis - Mathieu, Olivier (American Society of Plant Biologists, 2003)
In the Arabidopsis accession Columbia, 5S rDNA is located in the pericentromeric heterochromatin of chromosomes 3, 4, and 5. Both a major and some minor 5S rRNA species are expressed from chromosomes 4 and 5, whereas the genes on chromosome 3 are not transcribed. Here, we show that 5S rDNA methylation is reduced in 2-day-old seedlings versus 4-day-old or older aerial plant tissues, and the minor 5S rRNA species are expressed most abundantly at this stage. Similarly, when 5S rDNA is demethylated by 5-azacytidine treatment or via the decrease in DNA methylation1 (ddm1) mutation, the expression of minor 5S rRNA species is increased. We also show that in leaf nuclei of mature wild-type plants, the transcribed fraction of 5S rDNA forms loops that emanate from chromocenters. These loops, which are enlarged in nuclei of mature ddm1 plants, are enriched for histone H3 acetylated at Lys-9 and methylated at Lys-4 compared with the heterochromatic chromocenters. Up to 4 days after germination, heterochromatin is not fully developed: the 5S rDNA resides in prechromocenters, does not form conspicuous loops, and shows the lowest transcription level. Our results indicate that the expression and chromatin organization of 5S rRNA genes change during heterochromatin establishment.